الفطام النفسي لدى طالبات المرحلة الثانوية في مدينة بريدة في ضوء بعض المتغيرات الديموغرافية - الربدي، سفيان بن إبراهيم; البليهي، هيفاء بنت عبدالرحمن (جامعة سوهاج - كلية التربية, 2023)
هدفت الدراسة الحالية إلى التعرف على درجة الفطام النفسي لدى طالبات المرحلة الثانوية، ومقارنة الفروق بين متوسط درجات الفطام النفسي التي تعزى إلى مستوى تعليم الأم (أمية، تعليم عام، تعليم عال)، والتخصص الأكاديمي (العلوم الإنسانية، العلوم الطبيعية)، وتم استخدام مقياس الفطام النفسي (إعداد: الباحثان)، وقد طبقت الدراسة على طالبات المرحلة الثانوية بمدينة بريدة، وتكونت العينة من (400) طالبة موزعة بالتساوي بين طالبات الصف الثاني والثالث ثانوي. وأسفرت الدراسة عن النتائج الآتية: لدى طالبات المرحلة الثانوية درجة متوسطة من الفطام النفسي ككل، ودرجة متوسطة أيضا على جميع الأبعاد عدا بعد تحمل المسؤولية فقد كان مستواهن فيه مرتفع، وبينت عدم وجود فروق في درجة الفطام النفسي تعزى إلى مستوى تعليم الأم (أمية، تعليم عام، تعليم عالي) ذات دلالة إحصائية عند مستوى الدلالة (0.05) أو أقل منها بين استجابات الطالبات على درجة الفطام النفسي ككل وعلى جميع الأبعاد، باستثناء بعد التمركز حول الذات فقد كان الفرق لصالح الأمهات ذوات التعليم العام والتعليم الجامعي، وبالنسبة للفروق التي تعزى إلى التخصص الأكاديمي (علوم إنسانية، علوم طبيعية) فلم تظهر النتائج أي فروق ذات دلالة إحصائية في درجة الفطام النفسي الكلية وأبعاده، وفي ضوء هذه النتائج قدمت الدراسة مجموعة من التوصيات. The study aimed to recognizing the degree of psychological weaning among high school female students, and comparing differences between mean scores of psychological weaning that are ascribed to mothers' educational level (illiteracy, public education, or higher education), and the academic specialization (human sciences or natural sciences). and used the Psychological Weaning Scale (prepared by the researchers). the sample of study comprised (400) female students at Buraydah City. The study concluded the following results: the female students have a moderate degree of psychological weaning as a whole, and also a moderate degree at all dimensions except taking responsibility dimension in which their level was high. Concerning differences in psychological weaning degree that are attributed to mothers' educational level, there were no statistically significant differences, among the female students' responses as a whole, and at all dimensions, except for the self-centering dimension in which the difference was in favor of mothers who had public education and those who had higher education. As for differences that are ascribed to academic specialization, results did not indicate any statistically significant differences in the total score of psychological weaning and its dimensions. In the light of these results, the study introduced several recommendations.
Keywords: الصحة النفسية -- مرحلة المراهقة -- النمو النفسي -- الاستقلال النفسي